Improvement of methodological principles of financial resources management of enterprises in economy of Ukraine - Khalatur, Svetlana; Халатур, Світлана Миколаївна; Zubkova, Yuliia; Зубкова, Юлія (Полтавська державна аграрна академія, 2018)
The object of research is the financial and economic relations that arise in the process of managing financial resources of enterprises in the conditions of the national economy of Ukraine. One of the most problematic places is the need to describe the link between a competitive strategies of enterprises based on managing their financial resources. In the process of studying financial resources as an object of financial management, methods of induction and deduction, analysis and synthesis were used. On the basis of interpretation, system and retrospective analysis, observation, comparison and graphic representation of the results of the research, the estimation of dynamics and structure of financial resources of enterprises of Ukraine was carried out. In substantiating the recommendations on improving the financial resources management system of the subjects of entrepreneurship of the national economy of Ukraine, systematic methods, complexity, logical modeling, were applied. The research results show that there are certain links in the formation of competitive strategies of enterprises based on the efficiency of the use of financial resources. Enterprises of the national economy of Ukraine should formulate appropriate competitive strategies to improve their financial performance in a changing economic environment. It is necessary to know and apply appropriate strategies concerning the efficiency of using financial resources of enterprises: corporate development, functional level, resources and determinants of measuring financial efficiency in different economic periods. The effectiveness of managing the financial resources of enterprises of the national economy of Ukraine contributes to the ability to resilience to the threats that exist in their economic environment, and to ensure the continuous success of the enterprise. Thanks to the successful implementation of the methodological principles of financial resources management, it is possible to: reflect the synthesis of tools for increasing the cost of the enterprise (financial management); provision of flow management of financial resources; formation of value for all participants in the market and society (marketing); identification of factors and reserves for the creation of value (financial analysis); formation of information for empirical testing of evaluation models (accounting). Об’єктом дослідження є фінансово-економічні відносини, що виникають в процесі управління фінансовими ресурсами підприємств в умовах національної економіки України. Одним з найбільш проблемних місць є необхідність описати зв’язок між конкурентною стратегією підприємств на основі управління їх фінансовими ресурсами. В процесі дослідження фінансових ресурсів як об’єкта фінансового менеджменту були використані методи індукції і дедукції, аналізу і синтезу. На основі методів інтерпретації, системного і ретроспективного аналізу, спостереження, порівняння та графічного зображення результатів дослідження здійснювались оцінка динаміки та структури фінансових ресурсів підприємств України. При обґрунтуванні рекомендацій з удосконалення системи управління фінансовими ресурсами суб’єктів підприємництва національної економіки України були застосовані методи системності, комплексності, логічного моделювання. Результати дослідження показали, що існують певні зв’язки при формуванні конкурентних стратегій підприємств на основі ефективності використання фінансових ресурсів. Підприємства національної економіки України повинні формувати належні конкурентні стратегії, щоб покращити свої фінансові показники в мінливих економічних умовах. Слід знати та застосовувати відповідні стратегії, які стосуються ефективності використання фінансових ресурсів підприємств: корпоративний розвиток, функціональний рівень, ресурси та детермінанти вимірювання фінансової ефективності в різних економічних періодах. Ефективність управління фінансовими ресурсами підприємств національної економіки України сприяє здатності до можливостей і стійкості до загроз, які існують в їх економічному середовищі, та забезпечить безперервний успіх підприємства. Завдяки успішній реалізації методологічних засад управління фінансовими ресурсами забезпечується можливість: – відображати синтез інструментів зростання вартості підприємства (фінансового менеджменту); – забезпечення потокового управління фінансовими ресурсами; – формування цінності для всіх учасників ринку і суспільства (маркетингу); – виявлення факторів та резервів створення цінності та вартості (фінансового аналізу); – формування інформації для емпіричного тестування моделей оцінювання (бухгалтерського обліку).
Вдосконалення методологічних принципів управління фінансовим ресурсам підприємств у економіки України
Keywords: competitive strategies of enterprises; конкурентні стратегії підприємств; efficiency of management of financial resources; ефективність управління фінансовими ресурсами; national economy of Ukraine; національна економіка України